2015
DOI: 10.1021/acsphotonics.5b00416
|View full text |Cite
|
Sign up to set email alerts
|

Link between Cathodoluminescence and Electron Energy Loss Spectroscopy and the Radiative and Full Electromagnetic Local Density of States

Abstract: Electron energy loss spectroscopy (EELS) and cathodoluminescence (CL) have proved during the past few years to be tremendous tools to study surface plasmons in metallic nanoparticles, thanks to an extremely high spatial resolution combined with a broad spectral range. Despite their apparent close resemblance, qualitative differences between EELS and CL have been theoretically as well as experimentally pinpointed. We demonstrate that these differences are recovered when comparing the full electromagnetic local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
154
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(165 citation statements)
references
References 50 publications
11
154
0
Order By: Relevance
“…The sample was imaged by exciting the nanoparticle with energetic electrons (30 kV) in an SEM and collecting the radiation emitted as a function of the electron beam position. The spatially integrated CL emission across the PoM is shown in Figure c and closely resembles the measured dark‐field scattering spectra (see Figure S8 in the Supporting Information for additional CL data) . The CL map spectrally averaged ± 10 nm around the resonant wavelength is shown in Figure d.…”
Section: Purcell Enhancement and Near‐field Imagingsupporting
confidence: 66%
See 1 more Smart Citation
“…The sample was imaged by exciting the nanoparticle with energetic electrons (30 kV) in an SEM and collecting the radiation emitted as a function of the electron beam position. The spatially integrated CL emission across the PoM is shown in Figure c and closely resembles the measured dark‐field scattering spectra (see Figure S8 in the Supporting Information for additional CL data) . The CL map spectrally averaged ± 10 nm around the resonant wavelength is shown in Figure d.…”
Section: Purcell Enhancement and Near‐field Imagingsupporting
confidence: 66%
“…The spatially integrated CL emission across the PoM is shown in Figure 4c and closely resembles the measured dark-field scattering spectra (see Figure S8 in the Supporting Information for additional CL data). [50,51] The CL map spectrally averaged ± 10 nm around the resonant wavelength is shown in Figure 4d. The signal originates mostly at the edge of the nanoparticle, i.e., precisely in the region with the largest Purcell enhancement.…”
Section: Purcell Enhancement and Near-field Imagingmentioning
confidence: 99%
“…The absorption spectrum peaks at the natural frequency of 0.68 THz, whereas the peak of the scattering spectrum is around 0.75 THz. These kinds of shifts between scattering and absorption spectrum have been experimentally as well as theoretically reported in several papers [37][38][39]. The use of a good conductor at THz frequencies is manifested by the fact that the spectral absorption is far less than the scattering.…”
Section: Driven-damped Harmonic Oscillator Modelmentioning
confidence: 68%
“…Under these specific detection conditions, it was theoretically demonstrated that the signals delivered in this configuration of scanning near field optical microscope (SNOM) are proportional to the electric part of the photonic LDOS at the scanned positions of the point-like light source [9]. Note that we are leaving aside here electron microscopy tools like electron energy loss spectroscopy (EELS) which are also capable to access the photonic LDOS on a subwavelength spatial resolution [10][11][12].…”
Section: Introductionmentioning
confidence: 99%